2018
DOI: 10.23880/eoij-16000147
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of a PTO Shaft Used in an Agricultural Tractor

Abstract: This study describes a finite element method (FEM) based deformation simulation procedure for a power take off (PTO) shaft in an agricultural tractor. The agricultural tractor is a mobile power source in agricultural fields. The Agricultural tractor transmits power to the working implement through several systems independently. Most especially, rotary elements used in agricultural machinery take the required power and movement from the tractor take off (PTO) shaft. During this operation, the PTO shaft experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Chawla et al 65 found a difference of ∼1.02% between the analytical solution and the experimental work, and a difference of 1.05% between the FE method results and the experimental results. Celik et al 69 found a closeness of ∼7% between the % FEM results and the experimental results. 70 It is generally known that the allowable relative difference ratio of the FEA approach should be less than 10%.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Chawla et al 65 found a difference of ∼1.02% between the analytical solution and the experimental work, and a difference of 1.05% between the FE method results and the experimental results. Celik et al 69 found a closeness of ∼7% between the % FEM results and the experimental results. 70 It is generally known that the allowable relative difference ratio of the FEA approach should be less than 10%.…”
Section: Resultsmentioning
confidence: 69%
“…40 However, it should be noted that the variations between the experimental and simulation-based results may vary depending on the type of analysis, the level of geometry idealization, the FE model, and the boundary conditions created in an FEA. 69 When the experimental results and FEA results are compared, a ∼4% difference is found, as seen in Figures 31 and 32. This confirms that ANSYS results are particularly successful in 2D solution.
Figure 31. Analytical, experimental, and FEM solution comparison for three-point bending test.
Figure 32. Analytical, experimental, and FEM solution comparison for four-point bending test.
…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the stress and strain analysis of the static simulation showed the most stressed areas where there are stress concentrations on the DPFA and areas of expected breaks. These two criteria are important to improve the future design of machinery parts and practical experiments [27,28]. For instance, the stress analysis shows the areas where strain gages can be attached for practical experiments to obtain soil resistance force and straininduced on the DPFA.…”
Section: Fem Simulationmentioning
confidence: 99%
“…15,16 In the CAD process, design evolves with functionality, experience, and structural stress analysis. 17 Computer-aided engineering (CAE) finite element method software has been widely used. ANSYS software is the most comprehensive and widely used method; thus, it was adopted in this study.…”
Section: Introductionmentioning
confidence: 99%